Bambara groundnut, Vigna subterranea (L.) Verdc. - Heller, J.; Begemann, F.; Mushonga, J.; Leibniz Institute of Plant Genetics and Crop Plant Research; International Plant Genetic Resources Institute (1997)
Bambara groundnut (Vigna subterranea) is an indigenous African crop that has been cultivated for centuries from Senegal to Kenya, and from the Sahara to South Africa and Madagascar. Despite its drought tolerant properties, bambara groundnut has largely been ignored by the scientific community being regarded as a poor man's crop. This workshop represents an effort to coordinate efforts across Africa aimed at the conservation of genetic resources of V. subterranea and its development as a crop. Following a brief introduction and a bibliographical review, country reports are presented from 11 African countries detailing production, genetic resources and potential for breeding. These are followed by 6 papers each in two sections on agronomy and genetic resources, the recommendations of working groups and a report on the establishment of the International Bambara Groundnut Network. Four appendices include the workshop programme, a list of participants, addresses of bambara groundnut researchers, and institutions maintaining collections. (Abstract © CAB ABSTRACTS, CAB International)